2017
DOI: 10.16988/iuvfd.322981
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Malformations in French Bulldogs

Abstract: The aim of this study was to detect vertebral malformations among French Bulldogs admitted between the years 2011 -2016 due to the high popularity of the breed and the intentions to increase the breed welfare by reducing the occurrence of congenital anomalies. Besides, we aimed to look for gender predisposition, possible vertebral predisposition, occurrence of clinical symptoms and radiographic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…The incidence of CVM in French Bulldogs in this single-centre Australian study was higher than any other reported study with 100% of dogs having one CVM and 90% having ≥2 vertebral malformations, compared with incidence rates of 67%-93.5% in other studies. 1,7,9,20 However, the occurrence of more severe forms of CVM such as dorsal, lateral and dorsolateral aplasia was seen in 45% (14/31) of French Bulldogs in this study, yet these subtypes were not associated with neurological deficits. If these occurred in isolation, they may have been more significant (like in the Pug breed) but instead they were predominantly surrounded by other CVM, which may have attenuated the degree of kyphosis and scoliosis created by these more severe malformations, thus making them less significant.…”
Section: Discussioncontrasting
confidence: 48%
“…The incidence of CVM in French Bulldogs in this single-centre Australian study was higher than any other reported study with 100% of dogs having one CVM and 90% having ≥2 vertebral malformations, compared with incidence rates of 67%-93.5% in other studies. 1,7,9,20 However, the occurrence of more severe forms of CVM such as dorsal, lateral and dorsolateral aplasia was seen in 45% (14/31) of French Bulldogs in this study, yet these subtypes were not associated with neurological deficits. If these occurred in isolation, they may have been more significant (like in the Pug breed) but instead they were predominantly surrounded by other CVM, which may have attenuated the degree of kyphosis and scoliosis created by these more severe malformations, thus making them less significant.…”
Section: Discussioncontrasting
confidence: 48%
“…In this report, a young pug puppy was suspected of having spine malformation caused by hemivertebra. As literature data suggest, this breed and other brachycephalic breeds are predisposed to vertebral deformation (Moissonnier et al, 2011;Schlensker and Distl, 2013). The clinical signs in this dog appeared when the dog was just three and a half months old, which is earlier than described in other cases (Jeffrey et al, 2007;.…”
Section: Discussionmentioning
confidence: 60%
“…Although any breed can be affected, hemivertebra is a common abnormality in small brachycephalic screw-tailed breeds, such as English bulldog, French bulldog, Boston terrier and pug. This malformation can also be observed in Yorkshire terrier, West Highland white terrier, fox terrier, Pekingese and German pointer (Moissonnier et al, 2011;Schlensker and Distl, 2013;De Rycke and Saunders, 2017). Sex predisposition to this anomaly is not established, and it is thought to be a heritable disease that is autosomal recessive.…”
Section: Case Presentationmentioning
confidence: 99%
“…Lumbosacral CT abnormalities were recently described in this breed (as well as in other brachycephalic breeds) mostly including congenital malformations such as hemivertebrae, block vertebrae, transitional vertebrae, and spina bifida with a high prevalence of 51% 12,13 . Concurrent clinical signs with these malformations are variable 12,13 . Most dogs are neurologically normal with lumbosacral congenital malformations 13 .…”
Section: Introductionmentioning
confidence: 87%
“…Vertebral abnormalities are frequently seen in spinal imaging studies of French Bulldogs (FB), mostly involving thoracic vertebrae 1–11 . Lumbosacral CT abnormalities were recently described in this breed (as well as in other brachycephalic breeds) mostly including congenital malformations such as hemivertebrae, block vertebrae, transitional vertebrae, and spina bifida with a high prevalence of 51% 12,13 . Concurrent clinical signs with these malformations are variable 12,13 .…”
Section: Introductionmentioning
confidence: 99%